Using Granular Waste Tire as a Factor to Increase Shear Strength of Cohesionless Soils - Koray Aktürk; Öznur Karaca (Journal of Advanced Research in Natural and Applied Sciences)
Soils are called problematic soils when they do not have sufficient bearing strength to provide a founda-tion for the structures to be built on them and these types of soils need to be improved with appropriate methods depending on their properties. Improvement methods applied to strengthen soils often cause financial burden. Recently, there are studies about the use of waste rubber tires, which pose an environ-mental risk during storage, as a reinforcement material for soils. The main purpose of this study is to examine the effect of poorly graded sand (SP) mixed with granular waste tires in different proportions (10%, 20%, 30%, 40% and 50%) on the shear strength of the sand. For this purpose, the physical (water content, specific weight, unit weight) and mechanical (shear strength) parameters of the mixtures were determined. According to the results of the research, the material with 100% sand content contributes to the shear strength by a certain proportion when compared to the mixed materials containing granular-sized waste rubber. According to the results of this research, the highest slip resistance value was observed in material with 20% tire content in waste rubber sand mixtures, while higher rates of tire addition provided lower results than 100% sand material. In addition, considering the issue in terms of environmental im-pact, a column test was carried out on the mixture containing 20% rubber-80% sand and no adverse ef-fects of the pollutants were observed.